1990
DOI: 10.1093/carcin/11.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of radiation-induced transformation of C3H/10T1/2 cells by specific protease substrates

Abstract: In the current studies, we have examined the effect of two specific protease substrates, the thrombin substrate Boc-Val-Pro-Arg-MCA and the chymotrypsin substrate Suc-Ala-Ala-Pro-Phe-MCA, on the oncogenic transformation of C3H/10T1/2 cells induced with: (i) 6 Gy of X-radiation and (ii) 4 Gy of X-radiation followed by promotion with 12-O-tetradecanoylphorbol-13-acetate (TPA). Both substrates reduced radiation transformation while only Suc-Ala-Ala-Pro-Phe-MCA suppressed the TPA enhancement of radiation transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since the carcinogenesis process involves the participation of proteases and the anticarcinogenic action of protease inhibitors is attributed to their blocking action on these proteases Billings et al, 1990a ;Kennedy, 1993b), we examined the possibility of the oncosuppressive activity of the field bean protease inhibitor being related to its ability to inhibit the sarcoma cell proteases. For this, homogenates of sarcoma cells, isolated freshly from ascitic fluid were assessed for protease activity on gelatin containing zymograms.…”
Section: Resultsmentioning
confidence: 99%
“…Since the carcinogenesis process involves the participation of proteases and the anticarcinogenic action of protease inhibitors is attributed to their blocking action on these proteases Billings et al, 1990a ;Kennedy, 1993b), we examined the possibility of the oncosuppressive activity of the field bean protease inhibitor being related to its ability to inhibit the sarcoma cell proteases. For this, homogenates of sarcoma cells, isolated freshly from ascitic fluid were assessed for protease activity on gelatin containing zymograms.…”
Section: Resultsmentioning
confidence: 99%
“…In that case, the role of protease inhibitors in chemoprevention would be an indirect one. Billings et al (77)(78)(79) hypothesized that protease inhibitors inhibit cellular enzymes which induce or regulate transformation. It has been demonstrated that a potatoderived chymotrypsin inhibitor and soyabean derived Bowman-Birk inhibitor blocked the enzymatic cleavage of a peptide substrate (80) and thus suppressed malignant transformation.…”
Section: Mechanism Of Actionmentioning
confidence: 99%